The effectiveness of the logarithm module equipped with a Jigsaw-type cooperative model in improving learning outcomes - Lumbantoruan, Jitu Halomoan; Herman, Tatang (Journal of Education and Learning (EduLearn), 2025)
The teacher's job is to prepare learning plans, create modules, implement, assess, and evaluate. The fact that teachers don't have modules yet. As a result, the mean logarithmic learning outcome of 74.80 is below the standard of 75. It is urgent to research because there is a gap between theory, expectations, and reality. The aim is to produce a logarithmic module equipped with an effective jigsaw cooperative model. The method is the research and development (RD), analysis, design, development, implementation, and evaluation (ADDIE) model. There were 32 high school subjects. Data collection techniques using needs analysis instruments, and assessment instruments for material experts, teachers, and students. Collect student pre-test and post-test data. Analysis technique by calculating the mean of all module components, the mean of pre-test and post-test, and interpretation of each module component. As a result, the mean scores of material experts, teachers, and students were obtained at 92.35%, 91.45%, and 95.81% in the very good category. It was found that the mean learning outcomes of students who used the module were 90.28 and the mean of students who did not use the module was 68.40, with a difference of 25.48. In conclusion, the logarithm module is practical, and effective, and can improve student learning outcomes significantly.